2002
DOI: 10.1002/etc.5620210609
|View full text |Cite
|
Sign up to set email alerts
|

Fate of tributyltin in a created tidal wetland

Abstract: The ability of Spartina alterniflora to degrade tributyltin (TBT) in contaminated dredge spoils was investigated in a created wetland at Little Creek Naval Amphibious Base in Norfolk, Virginia, USA. Concentrations of TBT up to 250 ng/g did not inhibit S. alterniflora growth over a 16-month period. Disappearance rates of TBT in vegetated and unvegetated treatments were similar, with half-lives of 300 to 330 d. Disappearance rates were not constant, but they were correlated to temperature changes and were possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It was observed that TBT degradation is significantly faster (>40%) in vegetated than in nonvegetated sites (controls), the translocation to the aboveground tissues being very low. Ability of Spartina alterniflora to degrade TBT in contaminated dredged soils has been investigated in a created wetland (Anderson et al 2002). It has been observed that 0.25 mg kg −1 TBT did not inhibit plant growth over the 16-month period.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that TBT degradation is significantly faster (>40%) in vegetated than in nonvegetated sites (controls), the translocation to the aboveground tissues being very low. Ability of Spartina alterniflora to degrade TBT in contaminated dredged soils has been investigated in a created wetland (Anderson et al 2002). It has been observed that 0.25 mg kg −1 TBT did not inhibit plant growth over the 16-month period.…”
Section: Introductionmentioning
confidence: 99%